2021
DOI: 10.3389/fonc.2020.594388
|View full text |Cite|
|
Sign up to set email alerts
|

Post-Operative Complications and Nipple Necrosis Rates Between Conventional and Robotic Nipple-Sparing Mastectomy

Abstract: PurposeThis study is to directly compare surgical outcomes between conventional nipple-sparing mastectomy (CNSM) and robot-assisted nipple-sparing mastectomy (RNSM).Materials and MethodFor this case–control study, 369 cases of 333 patients who underwent CNSM or RNSM with immediate reconstruction between November 2016 and January 2019 at Severance Hospital in Seoul, Republic of Korea were reviewed. Patients with stage IV breast cancer (n = 1), receiving neoadjuvant chemotherapy (n = 43), or subjected to previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…For this reason, surgical techniques have evolved to reduce the possibility of this complication [ 5 , 6 ]. Despite the refinement of surgical techniques, a percentage of NAC lesions, which varies according to the various studies, is always present [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, surgical techniques have evolved to reduce the possibility of this complication [ 5 , 6 ]. Despite the refinement of surgical techniques, a percentage of NAC lesions, which varies according to the various studies, is always present [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, RNSM has the advantage of creating a hidden scar. In previous studies, the surgical safety and oncologic safety of RNSM were reviewed, and RNSM was not inferior to conventional NSM 15,25,26 . Further prospective studies are needed to evaluate the implications of RNSM 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…NAC ischemia and necrosis reportedly occur in 0–13% and 0–2.4%, respectively, of patients after RNSM with IBR [ 15 , 16 , 18 , 22 , 27 , 28 ]. NAC ischemia and necrosis can be caused by alterations in breast vascularity.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found a significant association between specimen weight and NAC-related complications in the univariate analysis but not in the multivariate analysis. This may be because the RNSM in this current study was performed on selected patients with small- to medium-sized breasts without ptosis [ 28 ], which is similar to patient recruitment in previous studies on RNSM [ 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%